Analisis Rekrutmen Calon Anggota Legislatif dalam Pemilu 2024: (Studi Kasus Partai Golkar Kabupaten Bogor) - Edwin Sena Andiana Gatot; Djoni Gunanto (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
This research aims to conduct a study in the 2024 Legislative Member Candidate Recruitment Analysis (Case Study of the Bogor Regency Golkar Party DPD). This research is an effort to find out how to analyze the recruitment of prospective legislative members in the 2024 elections (Case Study of the Golkar Party, Bogor Regency). Therefore, the method considered appropriate to use in this study is qualitative, descriptive analysis. The data collection technique through interviews is by asking a list of questions directly to the informant with the aim of obtaining data and information related to the Recruitment Analysis of Candidates for Legislative Members in the 2024 Election (Case Study of the Bogor Regency Golkar Party). The data collection instrument used to collect data is an interview guide containing a list of questions using a direct question and answer method with informants who are authorities on the object under study. Observation (observation) is a data collection technique, where the researcher makes direct observations of the research object to look closely at the activities carried out. This research found that from the three characteristics of the recruitment process above, the recruitment process carried out by the Bogor Regency Golkar party DPD was mixed in nature, combining top-dwon and bottom-up. We can see from the selection procedures listed in the DPP Decree Number: JUKLAK - 11/DPP/GOLKAR/V/2018 that the selection procedures begin with the selection team submitting a form of willingness to be nominated as a Candidate Member of the Regency DPRD to all members of the functionary cadre who have attended functionary orientation either organized by the Golkar Party DPP or the Regency Golkar Party DPD.